Correlational study of Hyperbilirubinemia as a diagnostic predictor for perforation in acute appendicitis - Papanaidu, Rishi; Chinta, Priyanka (Creative Pharma Assent, 2024)
Background: Appendicitis is an acute and life-threatening situation if not treated promptly encountered in surgery practice. Even today, most cases of appendicitis are diagnosed by clinical findings and imaging. Scanty information is available to diagnose the perforation of the appendix using serological tests; hence, an attempt is made. The present study aimed to find out the correlation of hyperbilirubinemia as a diagnostic predictor for perforation in acute appendicitis patients. Methods: This prospective observational study was conducted among patients diagnosed with acute appendicitis attending OPD of the general surgery department of Narayana Medical College Hospital. The duration of the study is between January 2023 and December 2023. A total of 400 patients with a diagnosis of either acute appendicitis or perforation were recruited into the study, and they collected blood samples for estimation of hyperbilirubinemia. Results: In the study population of 400 patients, 72 cases were diagnosed as appendicular perforation, and 328 patients had acute appendicitis. The cut-off value of hyperbilirubinemia was taken as serum bilirubin >1.0 mg/dl. Out of 72 cases of appendicular perforations, 64 patients have hyperbilirubinemia (89%), while in the acute appendicitis patients group, 82 of 328 patients have elevated serum bilirubin (25%). The observed mean values of serum bilirubin in the two groups were 1.74 and 0.89, and the difference in the standard error of the mean value of the two groups is statistically significant at a P-value of <0.001. Conclusions: Patients who presented with acute appendicitis symptoms and had serum bilirubin values >1.0 mg/dl had a higher probability of appendicular perforation. Hence, measuring serum bilirubin can be considered an additional diagnostic tool to existing clinical diagnosis and radiological evaluation for more precision in diagnosis.